2022
DOI: 10.1021/acs.jmedchem.2c00632
|View full text |Cite
|
Sign up to set email alerts
|

Improving Drug Delivery While Tailoring Prodrug Activation to Modulate Cmax and Cmin by Optimization of (Carbonyl)oxyalkyl Linker-Based Prodrugs of Atazanavir

Abstract: Structure–property relationships associated with a series of (carbonyl)­oxyalkyl amino acid ester prodrugs of the marketed HIV-1 protease inhibitor atazanavir (1), designed to enhance the systemic drug delivery, were examined. Compared to previously reported prodrugs, optimized candidates delivered significantly enhanced plasma exposure and trough concentration (C min at 24 h) of 1 in rats while revealing differentiated PK paradigms based on the kinetics of prodrug activation and drug release. Prodrugs incorpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Subsequent expansion of the structure–property relationship of this class of prodrugs led to optimized candidates 4v and 4w that substantially enhanced both AUC and C min of 3l . 213 The PK profiles of 4u–4w indicated that the circulating prodrugs acted as depots to provide a sustained release of 3l , representing a further advancement in the oral delivery of 3l over the previously-studied prodrugs. The examples provided by 4u–4w demonstrate the successful application of a prodrug strategy that mitigates not only the barriers to oral absorption of 3l , but also provides a measure of controlled parent release, in which the prodrug acts as a circulating depot of the parent that is released in a measured fashion by hydrolytic enzymes.…”
Section: Design Of Prodrugs To Mitigate Metabolismmentioning
confidence: 98%
“…Subsequent expansion of the structure–property relationship of this class of prodrugs led to optimized candidates 4v and 4w that substantially enhanced both AUC and C min of 3l . 213 The PK profiles of 4u–4w indicated that the circulating prodrugs acted as depots to provide a sustained release of 3l , representing a further advancement in the oral delivery of 3l over the previously-studied prodrugs. The examples provided by 4u–4w demonstrate the successful application of a prodrug strategy that mitigates not only the barriers to oral absorption of 3l , but also provides a measure of controlled parent release, in which the prodrug acts as a circulating depot of the parent that is released in a measured fashion by hydrolytic enzymes.…”
Section: Design Of Prodrugs To Mitigate Metabolismmentioning
confidence: 98%